If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y = 15 + -1y Solving 4y = 15 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 4y + y = 15 + -1y + y Combine like terms: 4y + y = 5y 5y = 15 + -1y + y Combine like terms: -1y + y = 0 5y = 15 + 0 5y = 15 Divide each side by '5'. y = 3 Simplifying y = 3
| 9y-5(y-2)=12 | | 2x^3-x^2-3x+1=0 | | -x^4+5x^3+3x^2-13x=10 | | 699=c*(1+.30) | | 699=c*.30 | | 160=t^2 | | 1500x=120000 | | 262=h^2 | | 7x^2=847 | | x^2+6-4=0 | | Q=40-2P | | 9m-4=-(18)+2m | | 6x+5=2x+-3 | | 6x-7x-3=15 | | y=4(1) | | 4b^2=256 | | 4y-(2y-1)=7 | | x^2+2x-143=0 | | 9y-14=26+13y | | 3=x+3-x | | 5-(8-c)=0 | | 7x=109.2 | | y=12x+420 | | 260=k(1300) | | 2x=12.25 | | 48=k(6) | | 8m-(6m-3)=9 | | 3n-(5n+2)=8 | | 12h-18=12h-18 | | 6(y+2)-2y=15 | | 2x+19=1x-80 | | 6-(3x-3)-[2(-4x-1)]=(-3x+2) |